Fox in socks - Seuss (Collins Picture Lions London, 2003)
In this hilarious book, the irrepressible Fox in Socks teaches a baffled Mr. Knox some of the slickest, quickest tongue-twisters in town. With his unique combination of hilarious stories, zany pictures and riotous rhymes, Dr. Seuss has been delighting young children and helping them learn to read for over fifty years